CHRONOLOGY AND CAUSE OF MASS MORTALITY EVENT ON FISH IN THE LOWER PART OF YAMAIMA RIVER, MIMIKA REGENCY, PAPUA - Husnah Husnah; Chairulwan Umar; Aroef Hukmanan Rais (Indonesian Fisheries Research Journal, 2018)
Mass mortality events (MMEs) on fish tend to increase recently both for cultured and wild fish both in coastal and inland waters. The MMEs on wild fish are mostly unknown. Mass mortality events on wild fishes of Mimika estuary, Papua have been recorded since long time ago and limited information was provided due to its remote area. A rapid appraisal study of mass mortality event (MME) of wild fishes chronology and cause was conducted in Yamaima river to Tifuka Estuary, Papua Province a week after the MME in April 2016. Seven sampling sites were selected. Two activities were conducted during the field survey: interview with the local people to get information on the chronology of the MME and collecting primary data on aquatic environment quality and fish samples. The occurance of goldstripe sardine inYamaima river and Tifuka estuary were triggered by the present of strong El Nino with ONI value more than 0.5oC in the ocean and atmosphere above Equator Pasific. Water quality at MME site was similar with remaining schooling fish and Tifuka estuary sites. Concentration of heavy metals in the sediment tend to decreased along with the distance from the MME site. Mass mortality of goldstripe sardinella could relate to oxygen suffocation as a result of disorentation movement of the fish shoals inaccordance with low tide and new moon phase. The number of the death goldstripe sardinella was estimated 200,000 fish with the weight of 18 tons. To mitigate MMEs in the future, efforts should be done such as: routine early detection of El Nino pattern and its effect on salinity and water temperature raising by placing key water quality parameter buoy in the mouth river of Papua and to set net or stack of logs in the cape area of west tailing levee Yamaima river to prevent the entrapment of migrating small pelagic fish specialy in the closed water area.